(untitled) (International Journal of Innovative Technologies in Economy, 2024)
This study aimed to explore the integration mechanism between Activity-Based Costing (ABC) and Target Costing (TC) as two modern tools for management control in economic institutions. The study concluded that the outputs of the ABC system represented by the vast amount of information and data on various production activities could effectively contribute to the implementation Target Costing system (TC). It recommended that economic institutions adopt an integrated costing system that combines Activity-Based Costing and Target Costing to enhance management efficiency and support cost-related decision-making.